2020
DOI: 10.3390/catal10080912
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesoporous Carbon as a Support of Pd Catalysts for CO2 Electrochemical Reduction

Abstract: Ordered mesoporous carbons (OMCs) have been used as catalyst supports of Pd nanoparticles for the electrochemical reduction of CO2 in 0.1 M KHCO3. OMC with tunable porosity and morphology were obtained by the hard-template approach using synthesized SBA-15 templates. SBA-15 materials were prepared using a mass ratio of the silica precursor (TEOS) and the surfactant (P123) of 2 or 5. After removing silica particles by a purification treatment with NaOH-ethanol or HF, different OMCs were obtained, with a develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Lázaro and co-workers synthesized Pd-doped porous carbon electrocatalysts using nano-casting, SBA-15 silica templating, impregnation (furan resin: carbon source and Na 2 PdCl 4 : Pd source), carbonization, chemical dissolution of silica, and chemical reduction processes. [122] The effect of silica precursor (TEOS) to surfactant (P123) mass ratio and the nature of the etching agent (HF vs NaOH-ethanol) on the structural ordering of the produced mesoporous samples were investigated. It was observed that increasing TEOS: P123 produced less ordered carbon structures due to the formation of noninterconnecting silica units that disrupted the structural ordering.…”
Section: Silica-derived Pgm-doped Carbon Co 2 Rr Electrocatalystsmentioning
confidence: 99%
“…Lázaro and co-workers synthesized Pd-doped porous carbon electrocatalysts using nano-casting, SBA-15 silica templating, impregnation (furan resin: carbon source and Na 2 PdCl 4 : Pd source), carbonization, chemical dissolution of silica, and chemical reduction processes. [122] The effect of silica precursor (TEOS) to surfactant (P123) mass ratio and the nature of the etching agent (HF vs NaOH-ethanol) on the structural ordering of the produced mesoporous samples were investigated. It was observed that increasing TEOS: P123 produced less ordered carbon structures due to the formation of noninterconnecting silica units that disrupted the structural ordering.…”
Section: Silica-derived Pgm-doped Carbon Co 2 Rr Electrocatalystsmentioning
confidence: 99%
“…Regretfully, the wide application of the catalyst was hindered by the limited reaction types, poor catalytic performance, and lack of effective preparation methods for completely metallic state PdNPs, which are proven to be active species. 33 , 34 …”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous carbon (MC) materials could improve the shortcomings of AC, such as insufficient anchor points and the aggregation and leaching of metal nanoparticles through the flexibly adjusted pore size. Also, the strong metal–support interactions triggered by the close contact of metal nanoparticles with the mesoporous material could improve the catalytic activity and stability. Because of the unique physiochemical properties of MC, the mesoporous carbon-supported palladium nanoparticle (PdNP/MC) catalyst has been studied with respect to traditional C–C coupling and hydrogenation reactions. Regretfully, the wide application of the catalyst was hindered by the limited reaction types, poor catalytic performance, and lack of effective preparation methods for completely metallic state PdNPs, which are proven to be active species. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation